Population based estimates of non-fatal injuries in the capital of Iran - Mafi Mostafa; Saadat Soheil; Sharif-Alhoseini Mahdi (BMC, 2011)
Abstract Background Fatal injuries are at the top of the injury pyramid; however, non-fatal injuries are quite common and impose huge medical expenses on the population. Relying on hospital data will underestimate the incidence of non-fatal injuries. The aim of this study was to estimate the annual incidence and out of pocket medical expenses of all injuries in urban population of Tehran (the capital city of Iran). Methods Using the cluster random sampling approach, a household survey of residents of greater Tehran was performed on April 2008. At randomly selected residential locations, interviewers asked one adult person to report all injuries which have occurred during the past year for all household members, as well as the type of injury, place of occurrence, the activity, cause of accidents resulting in injuries, the amount of out of pocket medical expenses for injury, and whether they referred to hospital. Results This study included 2,450 households residing in Tehran during 2007-8. The annual incidence of all injuries was 188.7 (180.7-196.9), significant injuries needing any medical care was 68.8 (63.7-74.2), fractures was 19.3 (16.6 - 22.4), and injuries resulted in hospitalization was 16.7 (14.2 - 19.6) per 1000 population. The annual incidence of fatal injuries was 33 (7-96) per 100,000 Population. In children aged 15 or less, the annual incidence of all injuries was 137.2 (120.0 - 155.9), significant injuries needing any medical care was 64.2 (52.2 - 78.0), fractures was 21.8 (15.0 - 30.7), and injuries resulted in hospitalization was 6.8 (3.3 - 12.5) per 1000 population. The mean out of pocket medical expense for injuries was 19.9 USD. Conclusion This population based study showed that the real incidence of non-fatal injuries in the capital of Iran is more than the formal hospital-based estimates. These injuries impose non trivial medical and indirect cost on the community. The out of pocket medical expense of non-fatal injuries to Tehran population is estimated as 27 million USD per year. Effective strategies should be considered to minimize these injuries and decrease the great financial burden to public and the health system.